Influence of corrugation angle in the stirred yoghurt processing in plate heat exchangers - Fernandes, Carla S. (2004)
Research on heat transfer of non-Newtonian fluids during thermal processing is useful to optimise the heat exchanger design, as well as to define quality levels of the final product. In the present study, a nonisothermal and non-Newtonian flow in plate heat exchangers was simulated numerically, in order to evaluate the influence of corrugation angle on the thermal and hydrodynamics characteristics of yoghurt during cooling in a plate heat exchanger (PHE). Cooling treatment of stirred yoghurt is usually carried out in PHEs since these equipments are suitable for liquid-liquid heat transfer duties that require uniform and rapid cooling or heating. In this operation, two mechanisms of heat transfer occur: conduction, in the plates, and convection inside the channels. The set of equations that describe mathematically the problem were the Navier-Stokes equations, for incompressible and stationary flow, and Fourier’s law for the conduction problems. Additionally, a constitutive model that describes the rheological properties of yoghurt under the cooling conditions has to be established in order to define totally the problem. The used model was proposed by Afonso et al. (2003) and takes into account the influence of shear rate and temperature